User Acceptance terhadap SIPADU-STIS Menggunakan Teori Technology Acceptance Model (TAM) dan Metode Analisis Structural Equation Modeling (SEM) - Abialam Koesnandy Hardjantho Hardjantho; Margaretha Ari Anggorowati (Jurnal Aplikasi Statistika & Komputasi Statistik, 2015)
The successful of developing and implementation of information sistem is dependon the user acceptance. SIPADU-STIS is an academic information system that support academic’s bisnis process. Technology Acceptance Model (TAM) will be employed for analysing of SIPADU-STIS system. Validation of TAM model will estimate using Structural Equation Model (SEM). The model shows that SIPADU-STIS has a high user’s acceptance .